Effect of toxic air pollutants on the cytokine release by leukocytes in patients with chronic obstructive pulmonary disease - A. U. Ishchanka (Медицинская иммунология, 2022)
Chronic inflammation in obstructive pulmonary disease develops in genetically predisposed individuals with prolonged or massive exposure to allergens or toxic air pollutants. This effect leads to hyperactivation of immune system and development of uncontrolled inflammatory response. The aim of the study was to determine the level of cytokines in the supernatant of leukocytes from the patients with COPD and asthma following incubation with air toxicants, i.e., a solution of cigarette smoke, an extract of cigarette tobacco, or a solution of exhaust combustion gases. The cytokines were determined by ELISA in the supernatants following exposure of peripheral venous blood leukocytes to the toxicants. To perform the assays, 10-mL samples of peripheral venous blood from the patients were taken into the test tubes with heparin (20 U/mL) in the morning time, not earlier than 2 days after therapeutic infusions of glucocorticosteroids. After gravity sedimentation, the leukocyte-rich was removed, centrifuged at 1500 rpm, then the liquid was discarded, and the leukocyte pellets were diluted with buffered saline (2 106 cells/mL). Individual leukocyte suspensions were divided into 4 wells of an immunological plate, 100 μL each. Equal volumes of test solutions simulating the effect of toxicants were added to three wells. The fourth well contained sterile isotonic sodium chloride solution (negative control). The mixtures in plates were exposed for 45 min at 37 °C followed by centrifugation for 10 min at 1500 rpm. From each well, 50 μL of the supernatant was taken and transferred to the plate for ELISA assays (under the same number). As a result, we have found that the solutions of cigarette smoke and exhaust gases caused release of IL-1β by leukocytes in the patients with asthma and COPD, but not in the samples from control group of healthy volunteers. Spontaneous increase in the IL-1β level was registered in the patients with asthma. The cigarette extracts caused an increased release of TNFα in the supernatant fluid of the patients with COPD. Upon exposure to a solution of exhaust gases, an increased level of TGF-β was revealed in patients with asthma compared to spontaneous cell activation (p < 0.05), as well as an increase in IFNγ contents in the patients with COPD as compared with control group (p < 0.05). No statistically significant changes were revealed for the levels of IL-6, IL-2, IL-4, IL-12, IFNα upon exposure of air toxicants on the leukocytes of patients with COPD, asthma or healthy volunteers.